Ontogenetic variation in the stratum granulosum of the epidermis of Chaetophractus vellerosus (Xenarthra, Dasypodidae) in relation to the development of cornified scales - Krmpotic, Cecilia Mariana (2014)
The epidermis of mammals is characterized by having a stratum granulosum that produces an orthokeratotic stratum corneum, different from the typical reptilian parakeratotic stratum. Nonetheless, some mammals show distinct degrees of parakeratosis in epidermal regions with few or no pilose follicles (e.g., areas subjacent to cornified scales). With respect to the epidermis and the development of cornified scales in the Dasypodidae, previous studies have supported the presence of a continuous stratum granulosum without any variations during ontogeny. This condition, in which the cornified scales develop without a loss of the stratum granulosum, was interpreted as primitive for eutherians. The present contribution expands the knowledge on the epidermis of Chaetophractus vellerosus in distinct ontogenetic stages in order to determine whether the cornified scales show the same developmental pattern as in other eutherians. The presence of a stratum granulosum in C. vellerosus neonates and its reduction in more advanced ontogenetic stages, in direct relationship with cornified scale development, supports the hypothesis that the partial parakeratosis in the xenarthran integument is secondary, as in other eutherians, and can be interpreted as a derived character state.